Analisis Pengaruh Risiko Pasar dan Risiko Operasional terhadap Pemberian Pinjaman - M. L., Juliana Ahmad; Arifin, Moch (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Based on the results of hypothesis test (t-test) variable Net Interset Margin (NIM) shows the value of significance 0.008> 0.05. This means that is rejected and is accepted, so it can be interpreted that there is no significant influence between Net Interset Margin (NIM) to Non Performing Loan (NPL). Based on the results of hypothesis test (t-test) variable Operational Cost Operating Income (BOPO) showed significant value of 0.001 <0.05. This means that is rejected and accepted, so it can be interpreted that there is significant influence between Operational Income Operating Cost (BOPO) to Non Performing Loan (NPL). Based on the results of research simultaneously, it can be concluded that the significant value of 0.003 less than 0.05, and the value of 7.136 which is greater than the 3.350, indicates that is rejected and is accepted, so it can be concluded that the NIM, BOPO variables together have a significant influence on the NPL.